2022
DOI: 10.1101/2022.03.23.22272804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Waning effectiveness of BNT162b2 and ChAdOx1 COVID-19 vaccines over six months since second dose: a cohort study using linked electronic health records

Abstract: Background The rate at which COVID-19 vaccine effectiveness wanes over time is crucial for vaccination policies, but is incompletely understood with conflicting results from different studies. Methods This cohort study, using the OpenSAFELY-TPP database and approved by NHS England, included individuals without prior SARS-CoV-2 infection assigned to vaccines priority groups 2-12 defined by the UK Joint Committee on Vaccination and Immunisation. We compared individuals who had received two doses of BNT162b2 or… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The included studies had a total sample of around one hundred million (N = 148260342) participants and of these, 74.2% were fully vaccinated ( n = 110076947) with at least two-doses of COVID-19 vaccines ( Table 1 ). Among the 13 studies, 1 study reported the effectiveness of the BNT162b2 (Pfizer–BioNTech), ChAdOx1 (AstraZeneca), mRNA-1273 (Moderna) and JNJ-78436735 vaccines ( 25 ); 1 study reported the effectiveness of the BNT162b2 and ChAdOx1 vaccines ( 24 ); 3 studies reported the effectiveness of the BNT162b2, ChAdOx1, and mRNA-1273 vaccines ( 12 , 21 , 22 ); 5 studies reported the effectiveness of the BNT162b2, and mRNA-1273 vaccines ( 14 , 16 , 17 , 20 , 23 ); 2 studies reported the effectiveness of the BNT162b2 vaccine ( 18 , 19 ), and 1 study reported the effectiveness of the mRNA-1273 vaccine ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies had a total sample of around one hundred million (N = 148260342) participants and of these, 74.2% were fully vaccinated ( n = 110076947) with at least two-doses of COVID-19 vaccines ( Table 1 ). Among the 13 studies, 1 study reported the effectiveness of the BNT162b2 (Pfizer–BioNTech), ChAdOx1 (AstraZeneca), mRNA-1273 (Moderna) and JNJ-78436735 vaccines ( 25 ); 1 study reported the effectiveness of the BNT162b2 and ChAdOx1 vaccines ( 24 ); 3 studies reported the effectiveness of the BNT162b2, ChAdOx1, and mRNA-1273 vaccines ( 12 , 21 , 22 ); 5 studies reported the effectiveness of the BNT162b2, and mRNA-1273 vaccines ( 14 , 16 , 17 , 20 , 23 ); 2 studies reported the effectiveness of the BNT162b2 vaccine ( 18 , 19 ), and 1 study reported the effectiveness of the mRNA-1273 vaccine ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this analysis, the effectiveness of the vector vaccine (ChAdOx1) was reported by in five studies ( 12 , 21 , 22 , 24 , 25 ). The pooled effectiveness of the vector vaccine was unable to be evaluated as most of these studies did not report the effectiveness of each vaccine individually.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations